Uptake and impact of climate-smart agriculture on food security, incomes and assets in East Africa - Radeny, Maren A.O.; Ogada, Maurice Juma; Recha, John W.M.; Kimeli, Philip; Rao, E.J.O.; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Increasing agricultural productivity and meeting food security needs in the face of climate variability and change in East Africa requires a range of technological, institutional and policy interventions. Climate-smart agriculture (CSA) is increasingly being used as an approach to integrated development. CSA refers to agriculture that sustainably increases agricultural productivity and livelihoods, resilience and adaptive capacity, reduces greenhouse gas emissions where possible, and enhances achievement of national food security and development goals. Since 2011, the CGIAR Research Program on Climate Change and Food Security (CCAFS) has been testing, evaluating and increasing access to and promoting a portfolio of CSA technologies and innovations across Climate-Smart Villages (CSVs) in East Africa. Using quasi-experimental approaches, this paper analyses the uptake and impact of CSA technologies (improved multiple stress-tolerant crop varieties, improved and better adapted livestock breeds and integrated soil and water conservation measures) on livelihood outcomes—food and nutrition security, incomes and asset accumulation, all of which are among the indicators of resilience.